2009
DOI: 10.1007/s12663-009-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparitive study of diclofenac transdermal patch against oral diclofenac for pain control following removal of mandibular impacted third molars

Abstract: Objective The objectives of this study was to evaluate subjectively the analgesic efficacy of Oral Diclofenac Sodium against Diclofenac Sodium Transdermal patch in the management of postoperative pain following surgical removal of impacted mandibular third molars. Materials and methods Twenty healthy subjects belonging to both the sexes in the age group of 18-40 years with bilateral mesioangular impactions of mandibular third molar teeth underwent surgical removal under local anaesthesia by administering an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 6 publications
(7 reference statements)
0
23
0
1
Order By: Relevance
“…In a study by Prithvi S Bachali et al . [ 10 ] where in transdermal diclofenac diethylamine (100 mg) patch group provided similar analgesia as oral diclofenac (100 mg) SR following the removal of mandibular impacted third molars on second and third postoperative day as measured on VAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Prithvi S Bachali et al . [ 10 ] where in transdermal diclofenac diethylamine (100 mg) patch group provided similar analgesia as oral diclofenac (100 mg) SR following the removal of mandibular impacted third molars on second and third postoperative day as measured on VAS.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, plasma levels achieved by transdermal patch ranged between 20 and 50 ng/ml, which was lesser when compared to the oral route, but these levels were sustained for a longer time. [ 10 ] One study has reported that the amount of drug bioavailable for targeting the sites of action is lower than oral route, but the absorbed dose appears to be adequate for therapeutic use. [ 19 ] In one in vitro study carried out in rats, patches were subjected to in vitro permeation enhancement studies through rat skin using, an especially designed diffusion cell.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in accordance with Prithvi et al . [ 1 ] who included twenty patients in which 13 were male (65%) and 7 (35%) were female.…”
Section: Discussionmentioning
confidence: 99%
“…On comparison of the pain at VRS between two groups and also within group comparison using Friedman test, in the diclofenac patch group, the difference in VRS pain scale at different visit was statistically significant with P = 0.001. This finding is in agreement with the study done by Prithvi et al .,[ 1 ] who evaluated the analgesic efficacy of oral diclofenac sodium against diclofenac sodium transdermal patch in the management of postoperative pain following surgical removal of impacted mandibular third molars. They used VAS and VRS scales for the evaluation and concluded that transdermal diclofenac sodium can be used as an alternative form of pain control following the removal of impacted mandibular third molars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation